Penerapan Asas Itikad Baik Dalam Perjanjian Jasa Titip Beli Barang Online - Nabila, Syadzwina Hindun (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: With advancements in technology and social media, consumers can easily obtain the goods they desire. With this convenience, customers can more quickly obtain the products they desire, whether through e-commerce, websites, or directly online with the seller. Not only easily obtainable items that are widely sold in the market, but also hard-to-find items, such as rare products or those only available abroad. This phenomenon encourages entrepreneurs to become more creative and create new business opportunities. One of them is by making a consignment agreement to buy goods, where the consignment gives authority to someone to spend on the desired goods with an agreed amount of money.Purposes of the Research:  The objective of this research is to examine the Application of the Principle of Good Faith in Online Shopping Service Agreements.Methods of the Research: This research is conducted normatively juridical, using library data as secondary data to examine the rules and norms in law.Results of the Research: The application of the principle of good faith is very important as the basis for the validity of an agreement because it is carried out with a balanced and proportional agreement between both parties, without favoring one party over the other. Since agreement is the determinant of the formation of a contract, there will be no contract between both parties if there is no agreement. Legal certainty is also very important to protect buyers who conduct online transactions through online escrow services and similar intermediaries. Because consumer rights are very important to uphold, and to raise business operators' awareness about the importance of consumer protection to foster honest and responsible business attitudes.